2010
DOI: 10.1111/j.1365-2249.2010.04164.x
|View full text |Cite
|
Sign up to set email alerts
|

Presence of intestinal helminths decreases T helper type 1 responses in tuberculoid leprosy patients and may increase the risk for multi-bacillary leprosy

Abstract: SummaryResistance to intracellular pathogens such as Mycobacterium leprae is dependent upon an effective T helper type 1 (Th1)-type immune response. On the other hand, intestinal helminths are known to subvert the host's immune response towards to either a Th2-type immune response or a regulatory T cell up-regulation, which may affect the host's ability to mount an effective response to mycobacteria. Here, we report a significant association between intestinal helminth infections and lepromatous leprosy [odds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 28 publications
1
39
1
2
Order By: Relevance
“…IFN-γ significantly decreases in the face of increased GI helminth infection intensity and increase after anthelminthic treatment [16]. Though our sample size was small and seasonal comparisons were nonsignificant, our approximately twofold decrease in mean IFN-γ signal in wet seasons when hosts were experiencing peak new GI helminth infections compared to in the relatively parasite-depleted dry season supports previous findings [15,16]. In addition, the significantly negative association between IFN-γ signal and animals with high GI parasite infections in conjunction with either high eosinophil counts or IgE titers lends support for opposing patterns between this Th1-type cytokine and parasites and parasite related immune factors, as would be expected in a parasite driven Th2-type immune skewing.…”
Section: Seasonal Immune Resource Allocationsupporting
confidence: 78%
See 1 more Smart Citation
“…IFN-γ significantly decreases in the face of increased GI helminth infection intensity and increase after anthelminthic treatment [16]. Though our sample size was small and seasonal comparisons were nonsignificant, our approximately twofold decrease in mean IFN-γ signal in wet seasons when hosts were experiencing peak new GI helminth infections compared to in the relatively parasite-depleted dry season supports previous findings [15,16]. In addition, the significantly negative association between IFN-γ signal and animals with high GI parasite infections in conjunction with either high eosinophil counts or IgE titers lends support for opposing patterns between this Th1-type cytokine and parasites and parasite related immune factors, as would be expected in a parasite driven Th2-type immune skewing.…”
Section: Seasonal Immune Resource Allocationsupporting
confidence: 78%
“…The pathways leading to and from Th1-type responses and Th2-type responses are mutually cross-regulated; thus, hosts have difficulty simultaneously mounting effective Th1 and Th2 responses [11,12]. Many studies have demonstrated that helminth infections are particularly adept at skewing immune responses toward the Th2 arm [11,13] and downregulating Th1 immunity even in the face of microparasitic coinfections [6,9,[14][15][16]. Chronic helminth infections may also cause host immunosuppression, resulting in maintenance of the immunomodulating worm infection [17] and increased susceptibility to coinfections [18].…”
Section: Introductionmentioning
confidence: 99%
“…34 Other studies have examined the effect of A lumbricoides infection on immunologic responses and outcomes among a cohort of patients with leprosy, another mycobacterial disease that depends on intact Th1 responses for control. 35 In comparison to patients with leprosy alone, those who were coinfected with intestinal helminths were more likely to have severe forms of leprosy and lower levels of IFN-γ. A mechanism that potentially explains helminth infection–related alterations in T-cell responses can be found from a study 11 that compared the immune activation status and cellular responses to purified protein derivative among people with and without chronic helminth infections from TB-endemic areas.…”
Section: Discussionmentioning
confidence: 96%
“…An association between intestinal helminth infections and lepromatous leprosy has been demonstrated with the frequency of intestinal helminths correlating strongly with the mycobacterial index [Diniz et al, 2010]. Evidence that Th1 downmodulation occurs during intestinal helminth infection was provided by the fact that intracellular IFN-g levels in both tuberculoid and lepromatous, helminth free leprosy patients, were approximately 2-fold higher than in helminth infected leprosy patients.…”
mentioning
confidence: 97%
“…Conversely, lepromatous patients harboring intestinal helminths produced close to 2-fold more IL-4 and IL-10 than helminth-free leprosy patients. These results suggest that a pre-existing infection by intestinal helminths may facilitate initial M. leprae infection or its progression to a more severe clinical form [Diniz et al, 2010].…”
mentioning
confidence: 98%